Suspension of the Operation of the CFE Treaty: a Legal Fact as a Teaching Aid - B. R. Tuzmukhamedov (Московский журнал международного права)
The article explores the interplay between international and Russian law underlining the suspension of the operation of the CFE Treaty by Russia It guides the reader through complexities of the applicable Russian legislation – from the Constitution to the Rules of Procedure of chambers of Parliament, that regulate treaty authority of branches of power.The article draws on the negotiating history of the Vienna Convention on the Law of Treaties in search of proof that a suspension of the operation of a treaty, while not specifically provided for in the treaty text, may still be an option for a party that desires to show its discontent with the way the treaty is implemented by others, without destroying the treaty, and to demonstrate its desire «to play by the rules».